2018
DOI: 10.1159/000497309
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus: Laboratory Methods for Isolation, Propagation, and Plaque Titration

Abstract: The human metapneumovirus (hMPV) is an important viral agent associated with severe infections of the upper and lower airways, especially in young children and immunosuppressed subjects. Nevertheless, in vitro studies of hMPV are very difficult due to the little knowledge we have on its laboratory manipulation. Objective: The aim of this study was to isolate and propagate hMPV from patients, and to establish a method to quantify the virus by plaque assay. Method: As part of a Latin American respiratory virus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Isolation of the A2 hMPV viral strain in this study showed initial CPE signs at the third blind passage, at 14 dpi, characterized by cell rounding and refractive cells clusters, consistent with previous reports [7,17]. Conversely, other authors have described that hMPV can appear as a syncytium [5,6,18], similar to RSV, and this difference may be related to the cell lines that were infected (e.g. LLC-MK2, tMK, MNT-1, A549) or to the viral genotype [19][20][21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Isolation of the A2 hMPV viral strain in this study showed initial CPE signs at the third blind passage, at 14 dpi, characterized by cell rounding and refractive cells clusters, consistent with previous reports [7,17]. Conversely, other authors have described that hMPV can appear as a syncytium [5,6,18], similar to RSV, and this difference may be related to the cell lines that were infected (e.g. LLC-MK2, tMK, MNT-1, A549) or to the viral genotype [19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…The isolation of A 2 hMPV viral strain, showed the first signs of CPE in the third blind passage, at 14 d.p.i, characterized by cell rounding and formation of refractive corsages of cells, similarly to what has been previously reported (Abiko et al, 2007; Boivin et al, 2002; Chan et al, 2003; Deffrasnes et al, 2005; Kinder et al, 2020). In contrast, other authors have described that hMPV can appear as a syncytium (Bernal et al, 2019; Sato et al, 2017; Van Den Hoogen et al, 2001; Yang et al, 2016) such as RSV (member of the same family) and this difference in CPE may be related to the cell lines that were infected (e.g. LLC-MK2) or to the viral genotype (Jumat et al, 2014; Nao et al, 2019; Reina et al, 2007; Tollefson et al, 2010; Williams et al, 2005; Zhang et al, 2012b).…”
Section: Discussionmentioning
confidence: 94%
“…At the same, as this new virus, is a concern for the world (at least it has already had a global economic impact), Latin America and even Colombia, among other regions and countries, Colombia faces an ongoing epidemic of dengue with over 130,000 cases, 1% of them severe, including more than 100 associated-deaths. When considering respiratory tract infections, multiple infectious agents are actively circulating, and will be increasing in the next few months in the region, including, those under surveillance, such as Influenza A (including AH1N1), Influenza B, human metapneumovirus, respiratory syncytial virus, adenovirus, parainfluenza 1, 2, 3 and 4, rhinovirus, bocavirus and enterovirus, among others [38][39][40] .…”
Section: Treatment and Preventionmentioning
confidence: 99%